Population Dynamics of Buffalo: The Effects of Droughts and Non-Equilibrium Dynamics - Hearne, J. W. (Ecology and Management of the African Buffalo, 2023)
Predation, poaching, disease and drought all impact African buffalo population numbers. Droughts in particular have important implications for the trajectories of animal populations, especially in tropical savannas. This is due to the pulse-like occurrence of droughts at intervals within the average lifespan of a buffalo. Consequently, populations are always in a state of transition and the proportions of the population in each age group are continually changing. We show that in these circumstances attempts to determine maximum stocking rates are prone to error. Furthermore, applying aggregated age groups to models may result in misleading forecasts of population trends. We believe this also holds for the populations of other mammalian species that live under so-called non-equilibrium conditions because their dynamics are then event-driven and not governed by factors such as density dependency.